Modelling sediment and total phosphorus export from a lowland catchment: comparing sediment routing methods. Issue 2 (26th February 2014) - Lu, Shenglan; Kronvang, Brian; Audet, Joachim; Trolle, Dennis; Andersen, Hans Estrup; Thodsen, Hans; van Griensven, Ann
Abstract Bank erosion is the main source of suspended sediment (SS) and diffuse total phosphorus (TP) in many lowland catchments. This study compared a physically based sediment routing method (Physical method), which distinguishes between stream bed and bank erosion, with the original sediment routing method (Original method) within the Soil and Water Assessment Tool (SWAT) version 2009, for simulating SS and TP losses from a lowland catchment. A SWAT model was set up for the lowland River Odense catchment in Denmark and calibrated against observed stream flow and phosphate (PO4) loads. On the basis of an initial calibration of hydrological and PO4 parameters, the SWAT model with the Original method (Original model) and the SWAT model with the Physical method (Physical model) were calibrated separately against observed SS and TP loads. The SWAT model simulated daily stream flow well but underestimated PO4 loads. The Physical model simulated daily SS and TP better than the Original model. The simulated contribution of bank erosion to SS in the Physical model (99%) was close to the estimated contribution from in situ erosion measurements (90–94%). Compared with the Original method, the Physical method is not only more conceptually correct but also improves model performance. Copyright © 2014 John Wiley & Sons, Ltd.